Rates and Timing of Telone II Application in Cotton - Jim Rich; David Wright (EDIS, 2003)
This document is ENY-675, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: February 2003.